Manisfestações de bullying em uma escola pública do ensino fundamental: uma análise pertinente - MATOS, Rita de Cássia Santana de (2024)
The present study aims to analyze the behavioral practices of students at a municipal public school and whether or not these are characterized as bullying. Starting from the following questions: when do adolescent behavioral practices become violence in the form of bullying? What are the impacts of this phenomenon on the lives of the individuals involved? The research is qualitative in nature, based on field research and the use of questionnaires to obtain data. For a more satisfactory development, the studies by Silva (2010), Souza and Almeida (2011), Fante (2005), among others, served as theoretical contributions. The research revealed that the manifestations occurring in the researched school are classified as practices of the bullying phenomenon, it also revealed that in the educational context, there are few scientific productions on this phenomenon, with vast productions focused on the clinical, psychological context, and in relation to school, which is where it spreads, the collection is limited. The practice of bullying is very serious, and should never be seen as a “joke”, the consequences generated by this phenomenon are devastating and some are irreversible, such as homicide and suicide.